A Complex Journey: Cell Wall Remodeling, Interactions, and Integrity During Pollen Tube Growth - Cascallares, Milagros; Setzes, Nicolás; Marchetti, Fernanda; López, Gabriel Alejandro; Distéfano, Ayelén Mariana; Cainzos, Maximiliano; Zabaleta, Eduardo; Pagnussat, Gabriela Carolina (Frontiers in Plant Science, 2020)
In flowering plants, pollen tubes undergo a journey that starts in the stigma and ends in the ovule with the delivery of the sperm cells to achieve double fertilization. The pollen cell wall plays an essential role to accomplish all the steps required for the successful delivery of the male gametes. This extended path involves female tissues recognition, rapid hydration and germination, polar growth and a tight regulation of cell wall synthesis and modification, as its properties not only change along the pollen tube but also in response to guidance cues inside the pistil. In this review, we focus on the most recent advances in elucidating the molecular mechanisms involved in the regulation of cell wall synthesis and modification during pollen germination, pollen tube growth and rupture.